Ranking Economists and Economic Institutions Using RePEc: Some Remarks - Christian Seiler; Klaus Wohlrabe (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
In socio-economic sciences the RePEc network (Research Papers in Economics) has become an essential source both for the spread of existing and new economic research. Furthermore the calculation of rankings for authors and academic institutions play a central role. We provide some cautionary remarks on the ranking methodology employed by RePEc and show how the aggregated rankings maybe biased. Furthermore we offer anew ranking approach, based on standardization of scores, which allows interpersonal comparisons and is less sensitive to outliers. We illustrate our new approach with a large data set provided by RePEc based on 24,500 authors.
Keywords: A12; A14; 330; Rankings; RePEc; ranking aggregation; standardization; Ökonomen; Wirtschaftsforschungsinstitut; Soziales Netzwerk; Internetportal; Bewertung; Ranking-Verfahren; Welt